Evaluasi Sistem Drainase Jatirejo – Ketapang Kecamatan Porong Paska Adanya Tanggul Lumpur Sidoarjo - Saves, Faradlillah (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2018)
Lapindo is the one big disaster in Sidoarjo which made two districts sunk, that was Tanggulangin and Porong district. There washigh embankment which made drainage was stopped, so the effect of drainage was flooded in Porong street and Malang’s railway. It happen, caused of the accumulation of water discharge in Jatirejo – Ketapang drainage. It was only the one canal which was going to the last drainage directly, without through the Lapindo’s embankment.The aim of this research is for knowing the existing discharge, the shelter capacity, and the alternative how to control the flooded in Jatirejo – Ketapang drainage’s canal, which has relation beetwen Lapindo’s embankment and Porong railways. Rainfall data used maximum the 10 last year, start from 2006 until 2015 (the source from 4 rain’s station Porong and Tanggulangin districts, such as Porong, Kedung cangkring, Kludan and Putat stations)There are many problems which was happened from Jatirejo – Ketapang canal’s drainage. for example, land’s reductionat several point, there are many mud sedimentation which come from the embankment, then so many weeds which reduce the Jatirejo – Ketapang drainage’s capacity directly. So, it is very important to remake some plan, normalization, and rehabilitation of Drainage canal’s Jatirejo – Ketapang. Keywords : Drainage, canal, mud, flooded